An analysis of the relationship between metastases and cachexia in lung cancer patients. (3rd August 2016) - Shiono, Masatoshi; Huang, Kan; Downey, Robert J.; Consul, Nikita; Villanueva, Nicolas; Beck, Kristen; Fenn, Kathleen; Dietz, Donald; Yamaguchi, Takuhiro; Kato, Shunsuke; Divgi, Chaitanya; Kalinsky, Kevin; et al.
Abstract: Weight loss and hematogenous metastases are poor prognosis factors in lung cancer patients that can but do not necessarily co‐occur. We retrospectively investigated the clinical association between cachexia, tumor characteristics (such as metastatic burden and mutational status), and treatment in lung cancer patients. The medical records of 394 lung cancer patients from two institutions (Columbia University, USA and Tohoku University, Japan) were reviewed. Information collected included the presence of cachexia, histologic subtype, tumor stage, number of metastases, mutation status, treatment, and survival. Descriptive statistics were performed. Only stage IV patients exhibited >5% weight loss (0.8%, 2.2%, 3.6%, and 5.1%, for stages I to IV; P = 0.0001). Patients with metastases developed cachexia more often than patients without metastases independent of treatment (6.0% and 7.1% weight loss in patients with metastases vs. 2.5% and 2.0% in patients without metastases, before [ P = 0.0001] and after [ P < 0.0001] treatment, respectively). The change in number of metastatic sites over time correlated with increasing weight loss (5.2%, 10.6%, 13.4%, and 13.4%, for an increase of 0, 1, 2, and ≥3 metastatic sites, from initial diagnosis to the endpoint; P < 0.0001). Patients with cachexia had worse survival than patients without cachexia (hazard ratio, 2.94; 95% confidence interval, 2.08–4.16; P < 0.0001). Tumors with mutated KRAS were associated with an increased risk of weight loss (11.4% weight loss in patients with mutated KRAS vs. 6.0% in patients with wild‐type KRAS; P = 0.0011). Our findings suggest that the capabilities of lung cancer to metastasize and cause cachexia might be linked intrinsically and are independent of treatments administered. KRAS‐mutated tumors were more commonly associated with cachexia. Abstract : We retrospectively investigated the clinical association between cachexia, tumor characteristics (such as metastatic burden and mutational status), and treatment in lung cancer patients. Our findings suggest that the capabilities of lung cancer to metastasize and cause cachexia might be linked intrinsically and are independent of treatments administered. KRAS‐mutated tumors are more commonly associated with cachexia.